Single-Molecule Imaging Reveals Rapid Estradiol Action on the Surface Movement of AMPA Receptors in Live Neurons - Godó, Soma; Barabás, Klaudia; Lengyel, Ferenc; Ernszt, Dávid; Kovács, Tamás; Kecskés, Miklós; Varga, Csaba; Jánosi, Tibor Z.; Makkai, Géza; Kovács, Gergely; Orsolits, Barbara; Fujiwara, Takahiro; et al. (Frontiers in Cell and Developmental Biology, 2021)
Gonadal steroid 17β-estradiol (E2) exerts rapid, non-genomic effects on neurons. Although E2 alters glutamatergic neurotransmission and synaptic plasticity, its non-genomic effects on AMPARs are unknown. Here, we analyzed the rapid effect of E2 on AMPARs using single-molecule tracking and super-resolution imaging techniques. E2 rapidly decreased the surface movement of AMPAR via membrane G protein-coupled estrogen receptor 1 (GPER1) in neurites in a dose-dependent manner. Activation of both GPER1 and estrogen receptor β by E2 was required to decrease the surface movement of AMPARs in somata. The cortical actin network plays a pivotal role in the GPER1 mediated effects of E2 on the surface mobility of AMPAR. E2 also decreases the surface movement of AMPAR both in synaptic and extrasynaptic regions on neurites and increases the synaptic dwell time of AMPARs. Our results provide evidence for understanding E2 action on neuronal plasticity and glutamatergic neurotransmission at the molecular level.